Emergency snake bite treatment devices, medical kits and related methods - Hack, Jason (My University, 2014)
First aid or emergency snake bite treatment devices include a belt or other securing member attached to a compression (bite isolation) member, the compression member having an outwardly projecting wall that is configured to surround the snake bite and compress the skin about the snake bite a distance inward to thereby isolate the venom from the bite to impede the venom from entering a victim's lymphatic system.
Keywords: poison; lymphatic; emergency